The Politics of Resilience: Transcending Reflections on Socio-Economic Vulnerability and Sustainable Development - Titang, Franklin (Advances in Social Sciences Research Journal, 2019)
The integration of the resilience concept into contemporary international development agendas is increasingly gaining acclamation amongst policy makers and international development agencies. It has been conceived as an operational trajectory for shock and crisis management especially for socio-economically vulnerable and deprived communities in Africa and beyond, and has surpassed boundaries, becoming more visible in various domains of development intervention including health, financial and environmental discourses. This paper discusses succinctly the malleability of the resilience paradigm within the sustainable development discourse and seeks to underscore the propensity of resilience to navigate across sectors by identifying the various contextualization and pathways in which it intersects with development. It highlights some positive variables of resilience but also denotes some contextual shortcomings, precisely the assumption that the concept is a constructive approach to poverty alleviation. However, the paper concludes that the in depth application of resilience with regards to context is imperative for a more sustainable anticipation of impending threats and crisis for vulnerable communities and societies.